Angiogenesis, Anti-Tumor, and Anti-Metastatic Activity of Novel α-Substituted Hetero-Aromatic Chalcone Hybrids as Inhibitors of Microtubule Polymerization - Sun, Moran; Wang, Yuyang; Yuan, Minghua; Zhao, Qing; Zhang, Yixin; Yao, Yongfang; Duan, Yongtao (Frontiers in Chemistry, 2021)
A library of new heteroaromatic ring linked chalcone analogues were designed and synthesized Of these, compound 7m with α-CH3 substitution and bearing benzofuran ring displayed the most potent activity, with IC50 values of 0.07-0.183 µM against three cancer cells. Its low cytotoxicity towards normal human cells and strong potency on drug-resistant cell revealed the possibility for cancer therapy. It also could moderately inhibit in vitro tubulin polymerization with an IC50 value of 12.23µM and the disruption of cellular architecture in MCF-7 cells was observed by an immunofluorescence assay. Cellular-based mechanism studies elucidated that 7m arrested cell cycle at G2/M phase and induced apoptosis by regulating the expression levels of Caspases and Parp protein. Importantly, compound 7m was found to inhibit the HUVECs tube formation, migration and invasion in vitro. In vivo assay showed that 7m could effectively destroy angiogenesis of zebrafish embryos. Furthermore, our data suggested that treatment with 7m significantly reduced MCF-7 cells metastasis and proliferation in vitro and in zebrafish xenograft. Collectively, this work showed that chalcone hybrid 7m deserves further investigation as dual potential tubulin polymerization and angiogenesis inhibitor.